The Effect of Foot Massage Therapy on Blood Pressure among Elderly with Hypertension - Abidah, Laila; Nurdiansyah, Tubagus Erwin; Rahman, Aulia (Genius Journal, 2026)
Introduction: Hypertension is a major public health problem and a leading cause of cardiovascular morbidity and mortality worldwide. Uncontrolled hypertension can lead to serious complications affecting the heart, brain, kidneys, and vision. In addition to pharmacological treatment, non-pharmacological interventions such as foot massage therapy have been proposed as complementary approaches to help reduce blood pressure. Objective: Therefore, this study aims to examine the effect of foot massage therapy on blood pressure among elderly patients with hypertension. Method: This study was a quasi-experimental research method with a one-group pretest-posttest design. The samples in this study were 20 elderly people aged 60 - 73 years who experienced hypertension Result: The results of this case study found that the application of foot massage therapy performed directly by the author to the subject can have an effect on changes in systolic and diastolic blood pressure values which are carried out routinely 5 consecutive days and show the average systolic blood pressure value before foot massage therapy is 170mmHg and diastolic blood pressure value of 100mmHg and has been done foot massage therapy, namely systolic blood pressure 130mmHg and diastolic blood pressure value 80mmHg Conclusion: Researchers analyzed using the sample paired test test and obtained a significance value of sig = 0.00 or sig<0.005 which can be concluded that there is an effect of giving foot massage therapy on lowering blood pressure in the elderly with hypertension at the Iringmulyo Health Center, Metro City in 2024.